Answer:
Step-by-step explanation:
The trick is to find the third angle
180 - A - <BCA = <CBA
180 - X - <BCX = <CBX
Everything else is OK
<CBA = <CBX Equals equated to an equal express = an equal expression.
Now by a little slight of hand, you get the two triangles to be equal by ASA, which always works.
Cheating you say? There is no such thing as cheating if it correct and it works.
Answer: Its little bit hard to become tutor. You need to give more answers.
Step-by-step explanation:
Answer:
50
Step-by-step explanation:
2x25=50-5=45
2yards= 72 inches
72 inches= 6 feet
so now that you know that, you know that she needs 6 feet and already has 3 feet. so she just needs 3 feet more. but they are asking for the answer to be in inches.
3 feet= 36 inches
your answer in 36 inches
The correct works are:
.![\frac{Blue(s + h) - Blue(s)}{h} = 4s + 2h](https://tex.z-dn.net/?f=%5Cfrac%7BBlue%28s%20%2B%20h%29%20-%20Blue%28s%29%7D%7Bh%7D%20%3D%204s%20%2B%202h)
<h3>Function Notation</h3>
The function is given as:
![Blue(s) = 2s^2 + 3](https://tex.z-dn.net/?f=Blue%28s%29%20%3D%202s%5E2%20%2B%203)
The interpretation when Steven is asked to calculate Blue(s + h) is that:
Steven is asked to find the output of the function Blue, when the input is s + h
So, we have:
![Blue(s + h) = 2(s + h)^2 + 3](https://tex.z-dn.net/?f=Blue%28s%20%2B%20h%29%20%3D%202%28s%20%2B%20h%29%5E2%20%2B%203)
Evaluate the exponent
![Blue(s + h) = 2(s^2 + 2sh + h^2) + 3](https://tex.z-dn.net/?f=Blue%28s%20%2B%20h%29%20%3D%202%28s%5E2%20%2B%202sh%20%2B%20h%5E2%29%20%2B%203)
Expand the bracket
![Blue(s + h) = 2s^2 + 4sh + 2h^2 + 3](https://tex.z-dn.net/?f=Blue%28s%20%2B%20h%29%20%3D%202s%5E2%20%2B%204sh%20%2B%202h%5E2%20%2B%203)
So, the correct work is:
![Blue(s + h) = 2s^2 + 4sh + 2h^2 + 3](https://tex.z-dn.net/?f=Blue%28s%20%2B%20h%29%20%3D%202s%5E2%20%2B%204sh%20%2B%202h%5E2%20%2B%203)
<h3>Simplifying Difference Quotient</h3>
In (a), we have:
![Blue(s + h) = 2s^2 + 4sh + 2h^2 + 3](https://tex.z-dn.net/?f=Blue%28s%20%2B%20h%29%20%3D%202s%5E2%20%2B%204sh%20%2B%202h%5E2%20%2B%203)
![Blue(s) = 2s^2 + 3](https://tex.z-dn.net/?f=Blue%28s%29%20%3D%202s%5E2%20%2B%203)
The difference quotient is represented as:
![\frac{f(x + h) - f(x)}{h}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%20%2B%20h%29%20-%20f%28x%29%7D%7Bh%7D)
So, we have:
![\frac{Blue(s + h) - Blue(s)}{h} = \frac{2s^2 + 4sh + 2h^2 + 3 - 2s^2 - 3}{h}](https://tex.z-dn.net/?f=%5Cfrac%7BBlue%28s%20%2B%20h%29%20-%20Blue%28s%29%7D%7Bh%7D%20%3D%20%5Cfrac%7B2s%5E2%20%2B%204sh%20%2B%202h%5E2%20%2B%203%20-%202s%5E2%20-%203%7D%7Bh%7D)
Evaluate the like terms
![\frac{Blue(s + h) - Blue(s)}{h} = \frac{4sh + 2h^2}{h}](https://tex.z-dn.net/?f=%5Cfrac%7BBlue%28s%20%2B%20h%29%20-%20Blue%28s%29%7D%7Bh%7D%20%3D%20%5Cfrac%7B4sh%20%2B%202h%5E2%7D%7Bh%7D)
Evaluate the quotient
![\frac{Blue(s + h) - Blue(s)}{h} = 4s + 2h](https://tex.z-dn.net/?f=%5Cfrac%7BBlue%28s%20%2B%20h%29%20-%20Blue%28s%29%7D%7Bh%7D%20%3D%204s%20%2B%202h)
Hence, the correct work is:
![\frac{Blue(s + h) - Blue(s)}{h} = 4s + 2h](https://tex.z-dn.net/?f=%5Cfrac%7BBlue%28s%20%2B%20h%29%20-%20Blue%28s%29%7D%7Bh%7D%20%3D%204s%20%2B%202h)
Read more about function notations at:
brainly.com/question/13136492